Durability of cement pastes exposed to external sulfate attack and leaching: Physical and chemical aspects. (February 2019) - Ragoug, Rim; Metalssi, Othman Omikrine; Barberon, Fabien; Torrenti, Jean-Michel; Roussel, Nicolas; Divet, Loïc; d'Espinose de Lacaillerie, Jean-Baptiste
Abstract: Sulfate ions in seawater or underground can attack the cement paste leading to expansion and strength loss. This expansion is usually related to ettringite and gypsum precipitation. This study aims to characterize the possible altered zone and to identify the mechanisms of degradation under such conditions. For this study, cement pastes manufactured using CEM I with two w/c ratios (0.45 and 0.60) were exposed to sodium sulfate solutions (semi-immersion at a controlled pH = 8.0 ± 0.1) after one year of curing in water. The analysis of the physical aspect of this phenomenon shows that two modes of transfer occur: transfer of sulfate ions to the cement matrix and leaching of calcium ions to the external solution. The analysis of the chemical composition of the affected material highlights the progressive consumption of portlandite at the surface, the decalcification of C-S-H and the formation of AFt from both Afm and aluminium incorporated in C-S-H. Highlights: In seawater, cementitious material are exposed to both ESA and leaching. ESA is characterized by the sulfate diffusion and its physicochemical fixation. This fixation occurs causing self-deceleration of the sulfate ingress in the material. Ettringite is formed from both AFm and aluminium incorporated in C-S-H. At low pH, the simultaneous formation of gypsum and ettringite can be highlighted.